2023
DOI: 10.1007/s11695-022-06415-z
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Serum Cortisol Level Is Predictive of Weight Loss After Laparoscopic Sleeve Gastrectomy in Men with Severe Obesity but Not Women

Abstract: Background Bariatric surgery is an effective treatment for severe obesity and its associated medical problems. Preoperative factors that predict postoperative weight loss remain to be fully characterized, however. Methods Anthropometric and laboratory data were collected retrospectively for severely obese patients who underwent laparoscopic sleeve gastrectomy (LSG) between April 2016 and July 2019 at our hospital. Preoperative factors that predicted weight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…The SG-associated improvement of the metabolic parameters could be explained by the effect of reduced gastric volume on the amount of ingested food and the subsequent weight loss that was evidenced to affect the patients’ biochemical and metabolic parameters, including glucose levels and lipid profile [ 44 ]. However, other hormonal changes may also share the metabolic effect after LSG [ 36 , 37 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…The SG-associated improvement of the metabolic parameters could be explained by the effect of reduced gastric volume on the amount of ingested food and the subsequent weight loss that was evidenced to affect the patients’ biochemical and metabolic parameters, including glucose levels and lipid profile [ 44 ]. However, other hormonal changes may also share the metabolic effect after LSG [ 36 , 37 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the same correlation was not observed in female patients. [14] The authors hypothesized that the absence of such a relationship in women may be attributed to the influence of estrogen on cortisol-binding globulin. In another study conducted by Ozturk et al, it was shown that preoperative basal cortisol levels were not useful in predicting postoperative weight loss.…”
Section: Discussionmentioning
confidence: 99%